Clíticos: variação da colocação pronominal no português em documento do século XVII - Helga Livia Aparecida Silva de Melo (2017)
This dissertation brings a contribution to the study of seventeenth-century Portuguese language, by means of a detailed description of the clitic placement in 83 letters written by the Queen Catarina de Bragança, between 1685 and 1692. It is considered a valuable corpus, because it is authograph, original and nearly unknown to linguistic research. In these letters, all the occurrences of clitics were collected, taking into account their host verbs. The occurrences were classified according to the clitic placement (proclisis or enclisis) and according to the types of sentence. The analysis was made according to the finite (indicative, subjunctive and imperative) and non finite (gerund and infinitive verbal forms and to types of verbal periphrases (with past participle, gerund, or infinitive). The interpolation was analyzed separately. On the basis of the apparent variability between proclisis and enclisis, a detailed description of the syntactic contexts in which the choice between one or the other variant form determined by syntactic factors has been made , and also a description of the syntactic context in which the alternance was possible. When the host verb is in the indicative mode, in variation contexts, we have the predominance of proclisis (86%). When the host verb is in the infinitive, the variation occurred in favor of the enclisis (55,7%). Considering the clitic placement as a grammatical indicator of the linguistic change that has occurred in European Portuguese, this description reveals a more conservative grammar, since it maintains some patterns that would become obsolete in the following centuries. The generalized use of proclisis in finite clauses is a context that the current grammar is predominantly enclitic.